2018
DOI: 10.1002/cpe.4420
|View full text |Cite
|
Sign up to set email alerts
|

A survey of techniques for architecting SLC/MLC/TLC hybrid Flash memory–based SSDs

Abstract: Flash memory-based solid-state drives (SSDs) offer several attractive features and benefits compared to hard disk drive (HDD), such as shock resistance and better performance especially for random data access. Depending on the number of bits in each cell, Flash memory can be designed as single/multi/triple level cell (SLC/MLC/TLC), which have different performance, density, cost and write endurance characteristics. To bring the best of these together, several researchers have proposed designing SSD using hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…We classify the works based on key parameters to highlight their similarities and differences. We believe that the techniques reviewed here will also be useful for current and future lifetime-limited or write-agnostic memories such as Flash memory [42]. We conclude this paper with a brief mention of future research challenges.…”
Section: Conclusion and Future Outlookmentioning
confidence: 94%
“…We classify the works based on key parameters to highlight their similarities and differences. We believe that the techniques reviewed here will also be useful for current and future lifetime-limited or write-agnostic memories such as Flash memory [42]. We conclude this paper with a brief mention of future research challenges.…”
Section: Conclusion and Future Outlookmentioning
confidence: 94%
“…Three-dimensional structure technology [ 2 ] is committed to transforming a planar structure into a three-dimensional structure, which increases the storage capacity under the same area. Multi-bit memory cell technology [ 3 ] focuses on improving the number of bits in the storage unit in order to achieve a multiple increase in storage capacity. With gradual in-depth study of the two technologies, researchers have found that while the storage density of NAND flash memory has doubled, the data reliability problem has worsened.…”
Section: Introductionmentioning
confidence: 99%
“…However, many data classification and allocation techniques for hybrid SSDs are not suitable for the access characteristics of an LSMKV. Many previous techniques have classified data that are frequently written to the same logical address as hot data and allocate them to fast storage spaces [1], [7]- [9], [13], [18], [20], [22]. LSMKVs write key-value data to adjacent logical addresses even if the write operation is an update to the key-value data in the storage [10], [16].…”
Section: Introductionmentioning
confidence: 99%